3xkwadrat-2(pierwiastek3x)+1
2)6xkwadrat -12
3)27+y do potegi 3
4)x3-9x2+27x-27
(x2+2x+4)(x-2)2
6)(x-1)(x2+x+1)(x3+1)
7)(9x4-3x2+1)(3x2+1)
równania i nierówności
1)8-x2>0
2)-1/25*x2>0
3)x2=4x
4)3+x2<0
5)49=-4x2
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Δ = b²-4*a*c
x₁ = (-b-√Δ)/2a
x₂ = (-b+√Δ)/2a
1)
3x²-2(√3x)+1
3x²-2√3x+1
a=3 b =2√3 c=1
Δ = (2√3)²-4*3*1 = 12-12 = 0
x = (-2√3)/ 6 = -⅓√3
2)
6x² -12
6x² =12 |:6
x² = 2
x = √2
3)
27+y³
y³ = -27
y = -3
4)
x³-9x²+27x-27
x²(x-9)+27(x-1)
(x²+27)(x-9)(x-2) = 0
x² = -27 x∉
x = 9
x = 2
5)
(x²+2x+4)(x-2)² = (x²+2x+4)(x²-4x+4)
Δ = 4-4*1*4 = -8
Δ = 16-4*1*4 = 0
x = 4/2 = 2
6)
(x-1)(x²+x+1)(x³+1)
x = 1
Δ = 1-4*1*1 = 1-4 = - 3
x = -1
7)
(9x⁴-3x²+1)(3x²+1)
x² = t
9t²-3t+1 = 0
Δ = 9-4*9*1 = 9-36 = -27
3x² = -1 |:3
x²=-1/3
x∉
równania i nierówności
1)8-x²>0
x² < 8
x < √8
2)
-1/25*x²>0
x² > 1/25
x > ±1/5
3)
x²=4x
x²-4x = 0
x(x-4)
x = 0
x = 4
4)
3+x²<0
x²<-3
x∉
5)
49=-4x² |:(-4)
x² = -12,25
x ∉
W załączniku.